1992
DOI: 10.2151/jmsj1965.70.1b_177
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Asian Monsoon on the Interannual Variability of the Global Climate System

Abstract: The role of the Asian summer monsoon on the interannual variability of the global climate system particularly relevant to the ENSO time scales is discussed, by examining the statistical and dynamical links between the Asian summer monsoon, the atmosphere/ocean system in the tropics and the westerly flow regimes in the extratropics.The Asian monsoon, the ocean and the atmosphere in the tropical Pacific are tightly linked together as one climate system, named here as the MAOS (Monsoon and the Coupled Atmosphere/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…El Niño-southern oscillation (ENSO) has a vigorous impact on the change of mid-latitude westerly regimes (Yasunari and Seki, 1992). If the interannual variation of the snow-cover extent is closely linked to the tropospheric circulation, the modulation of the westerly jet due to the ENSO phenomenon may change the summer monsoon activity through land-atmosphere interaction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…El Niño-southern oscillation (ENSO) has a vigorous impact on the change of mid-latitude westerly regimes (Yasunari and Seki, 1992). If the interannual variation of the snow-cover extent is closely linked to the tropospheric circulation, the modulation of the westerly jet due to the ENSO phenomenon may change the summer monsoon activity through land-atmosphere interaction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was suggested that the relationship has weakened since the 1980s and one explanation was that increasing mid latitude continental temperatures have favoured strong monsoons (Kumar et al, 1999). Another possibility may be related to decadal variations of the NAO which is found to be a significant mechanism affecting Asian monsoon and El Niñ o relationships (Yasunari and Seki, 1992).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies by Yang (1996) and Yang and Lau (1998) suggest that El Niñ o plays a more significant role in Indian monsoon rainfall anomalies than Eurasian winter snow cover and related soil moisture. Yasunari and Seki (1992) proposed that the interactions between Asian summer monsoon and El Niñ o are strongly modified by the North Atlantic Oscillation (NAO) which stochastically amplifies or dampens the biannual nature of the monsoon and the coupled tropical atmosphere/ocean system. In summary, it seems that (i) snow volume (or depth) has a more significant connection to summer monsoon rainfall than snow coverage; (ii) the teleconnections between winter snow and summer rainfall are geographically dependent; and (iii) abnormal SSTs over the eastern tropical Pacific interact with Eurasian snowfall and monsoon rainfall through extratropical atmospheric circulation.…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests the contribution of diatoms to TOC was less and that from other phytoplankton was significant before 1.2 Ma ago. The upheaval of the Himalayas around 1.2 Ma ago has been considered to cause a big climate change (Yasunari and Seki, 1992), and the second cooling event in the Baikal record occurred 1.8 Ma ago . Such big climate changes may correspond to the diminution of dinoflagellate and green algae.…”
Section: Resultsmentioning
confidence: 99%